Business intelligence : data mining and optimization for decision making - Vercellis, Carlo (Chichester, U.K : Wiley, 2010)
Business Intelligence' provides coverage of topics currently dispersed throughout data mining and business books, bringing them together for the first time to provide readers with an introductory and practical guide to the mathematical models and analysis methodologies vital to business intelligence
Includes index
BSBA
Keywords: Decision making -- Mathematical models; Business intelligence; Data mining